2009
DOI: 10.1002/anie.200903893
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry with Selenium Reagents: Development of Efficient Catalytic Reactions

Abstract: cyclizations · homogeneous catalysis · oxidation · seleniumApplications of selenium reagents in organic chemistry have developed rapidly over the past years, and comprehensive reviews on this area have appeared.[1] Rather new, however, is the use of selenium-based catalysts in organic synthesis. We highlight new developments in organoselenium catalysis and in particular the use of selenium electrophiles and organoselenium compounds in carbonylation reactions and the oxidation of alkenes and carbonyl compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
100
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(102 citation statements)
references
References 40 publications
0
100
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Due to their unique properties, they attracted a wide interest as reagents in new synthetic routes, 3 promising catalysts for various oxidation reactions [1][2][3][4][5][6][7][16][17][18][19] and potential pharmaceuticals. [8][9][10][11][12][13][14][15]20,21 Ebselen (2-phenylbenzisoselenazol-3(2H)-one) and its analogues have received particular attention as glutathione peroxidase mimics, 8,11,15 antioxidant and anti-inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Due to their unique properties, they attracted a wide interest as reagents in new synthetic routes, 3 promising catalysts for various oxidation reactions [1][2][3][4][5][6][7][16][17][18][19] and potential pharmaceuticals. [8][9][10][11][12][13][14][15]20,21 Ebselen (2-phenylbenzisoselenazol-3(2H)-one) and its analogues have received particular attention as glutathione peroxidase mimics, 8,11,15 antioxidant and anti-inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover diselenides can be easily oxidized in situ by hydrogen peroxide to seleninic acid or peroxyseleninic acid, which are in some cases excellent catalysts in the oxidation of organic compounds [21][22][23][24], as, for instance, epoxidation reaction of alkenes [25], Baeyer-Villiger reaction [26], oxidation of carbonyl compounds [27], dehydrogenation of carbonyl compounds [28][29], oxidation of secondary amines [30][31], oxidation of imines [32], or selenenylations or halogenations [33].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the use of inorganic selenoxide (SeO2) for the catalytic allylic oxidation of olefins was reported by Sharpless in 1977 [45] and it was later demonstrated that the same catalyst, in the presence of hydrogen peroxide as an oxidant in a mixture of water and dioxane, can convert olefins into the corresponding diols [46], it was only in 2009 that the use of organoselenium catalysts was, for the first time, claimed as a convenient, green alternative to conventional stoichiometric protocols or metal-catalyzed reactions [47]. These opened the way for a series of applications designed in order to address the principle of Green Chemistry, and a number of interesting results obtained during the last five years were recently collected in a review article [1].…”
Section: Water As An Alternative Medium For Organoselenium-catalyzed mentioning
confidence: 99%